The Detection of Kidney Injury in Dogs by Biomarker: Neutrophil Gelatinase-Associated Lipocalin (NGAL) - วัฒนพรภิรมย์, ธนากร; เล็กเจริญสุข, เฉลิมพล; สินธุสิงห์, ชยกฤต (Journal of Mahanakorn Veterinary Medicine, 2018)
Acute kidney injury commonly causes the high risk of death in dogs because the clinical investigation by blood urea nitrogen and creatinine has failed to identify early stages of kidney dysfunction and structural injury. By this reason, there is important to use the biomarker for diagnosis of early kidney injury and immediate treatment. The objective of this research was to investigate the application of Neutrophil Gelatinase-Associated Lipocalin (NGAL) canine biomarker, a protein that is increasing when renal tubular cells damage resulted for the acute kidney injury and kidney diseases in dogs. The studied dogs were classified into three groups according to canine IRIS guidelines for grading AKI. Group 1 was defined as 1-7 years-old dogs without clinical or laboratory signs of AKI. Group 2 was defined as dogs with kidney injuries and normal creatinine values (IRIS AKI, 2013, grade I with serum creatinine ≤1.6 mg/dl). Group 3 was defined as renal failure dogs with elevated serum creatinine (IRIS AKI grade II–V with serum creatinine >1.6 mg/dl). Serum and urine samples were taken for NGAL evaluation (sNGAL and uNGAL, respectively) with Dog NGAL ELISA kit (BIOPORTO®, Denmark). The results found that the means of sNGAL and uNGAL in the dogs with kidney injuries and normal creatinine values were higher than normal dogs. It seems that the renal damages in the dogs with kidney injuries and normal creatinine values were severe than normal dogs. In this result, sNGAL could be effective to predict the acute renal injury better than creatinine level. Furthermore, the means of sNGAL and uNGAL were similar in the dogs with kidney injuries and normal creatinine values. Likewise, the level of uNGAL was increased more rapidly than the sNGAL level in dogs with renal failure and elevated serum creatinine compared to normal dogs. This indicated that uNGAL was better than sNGAL for evaluation of acute renal injury. This study showed that NGAL may serve as the marker for prediction of kidney injury, detection of different kidney diseases and evaluation of treatment outcome in dogs.